State of viral hepatitis care in 16 countries of Central and Eastern European Region - Chkhartishvili, Nikoloz; Holban, Tiberiu; Simonović Babić, Jasmina; Alexiev, Ivailo; Matičič, Mojca; Kowalska, Justyna; Horban, Andrzej (Central European Journal of Public Health, 2019)
OBJECTIVES: Survey was conducted to assess state of viral hepatitis care in Central and Eastern Europe (CEE). METHODS: Representatives of 16 CEE countries completed on-line survey in April-May 2017 that collected information on basic epidemiology and availability of key services for HCV and HBV infections. Sources of information provided ranged from national surveillance data to expert opinion. RESULTS: The burden of viral hepatitis varied between countries, ranging from 6,500 to 2 million for HCV and from 10,000 to 3 million for HBV. Access to routine HCV RNA testing and genotyping was reported by 11 and 9 countries, respectively. HCV resistance testing was available in 7 countries. Direct acting antivirals (DAAs) were available in 13 countries, most frequently Sofosbuvir and Ledipasvir/Sofosbuvir (12 countries apiece) and Ombitasvir/Paritaprevir/Dasabuvir (9 countries). HBV DNA testing and HBV genotyping were routinely available in 10 and 7 countries, respectively. Eleven countries reported available treatment with Tenofovir. CONCLUSIONS: There are gaps in viral hepatitis care in CEE. Despite the availability of registered modern drugs for HCV and HBV, the access to treatment is limited. Ensuring quality health care is essential to reduce the epidemic and achieve the WHO's goal of eliminating viral hepatitis as a major public health challenge.
Keywords: Antiviral Agents; hepatitida B; lidé; Europe; hepatitida C; Evropa; Hepatitis B; východní Evropa; Hepatitis C; Europe, Eastern; antivirové látky; Humans